Disability and Bureaucratic Forms of Life - Thomas Abrams (Nordic Journal of Science and Technology Studies, 2015)
This paper employs a hybrid actor-network theory/phenomenological approach to a frequent bother in the lives of disabled persons: bureaucratic forms. I argue that these forms are key sites where disabled personhood emerges, something I examine through the lens of what philosopher Annemarie Mol calls ‘ontological politics’. To be disabled is to be entered into the bureaucratic form of life. These forms translate human existence into a categorize-able, transportable and combinable object, to be administered through ‘centers of calculation’. Combining Heidegger’s fundamental ontology with Latour’s theory of paperwork, I suggest that these forms represent disability in terms of ‘objective presence’, as a mere pre-existing thing, rather than a human way of being. I conclude with suggestions for further phenomenological research that takes embodied difference as its point of departure.